Federico : one man's remarkable journey from Tututepec to L.A. - Jiménez Caballero, Federico, 1941- (The University of Arizona Press, 2021)
"This edited autobiography is a frank and intimate account of over seventy-six years in the life of Federico Jimenez Caballero, a man with deep indigenous roots in which the supernatural is blended with the practical in everyday life. Jimenez Caballero's story is told in the first person based on his memories and real-life experiences as a man of mixed heritage who identifies with both his Mixtec indigenous culture as well as his Mestizo side of the family. As a child growing up in a rural, peasant village in Mexico, Jimenez Caballero faced challenges that most of us cannot even imagine yet alone overcome; as a young adult he never stood still but instead depended on his survival skills and sheer will to become the successful person he was predicted to be at his birth. In the United States, Jimenez Caballero has created an identity that bridges his Mexican indigenous heritage with the overall Latino culture of southern California. Through all of his trials and tribulations he created a successful life for a young indigenous boy who had grown up in a culturally mixed, Mestizo-indigenous, peasant village where the cows and horses had to be chased off a grass landing strip. From these humble beginnings he moved up to the bright lights and fame as a jewelry artist to the stars in Hollywood. Jimenez Caballero's success as an entrepreneur and artist opened doors where he connected with the wealthy elite and became a celebrated philanthropist. The manuscript includes a brief personal introduction by Shelby Tisdale, editor of the manuscript, that focuses on her relationship with Jimenez Caballero, providing a glimpse into his Mixtec past and how it relates to his family heritage"--